THE TASK OF FREE VIBRATIONS OF HIGH-RISE BUILDINGS WITH A CYLINDRICAL RESERVOIR WITH FLUID (Archive of Conferences, 2021)
At the article theoretical investigates the problem of the transverse vibration of a high-rise structure carrying two concentrated masses using an integral transformation. The solutions of the frequency equation are obtained.